2017
DOI: 10.1007/978-3-319-52471-9_23
|View full text |Cite
|
Sign up to set email alerts
|

Root-counting Measures of Jacobi Polynomials and Topological Types and Critical Geodesics of Related Quadratic Differentials

Abstract: Two main topics of this paper are asymptotic distributions of zeros of Jacobi polynomials and topology of critical trajectories of related quadratic differentials. First, we will discuss recent developments and some new results concerning the limit of the root-counting measures of these polynomials. In particular, we will show that the support of the limit measure sits on the critical trajectories of a quadratic differential of the form Q(z) dz 2 = az 2 +bz+c (z 2 −1) 2 dz 2 . Then we will give a complete clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Finally we note that our work (see Example 2) provides a family of counterexamples to Conjecture 1 in the recent paper by Shapiro and Solynin [19].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Finally we note that our work (see Example 2) provides a family of counterexamples to Conjecture 1 in the recent paper by Shapiro and Solynin [19].…”
Section: Introductionmentioning
confidence: 53%
“…The characteristic polynomial of (5.5) is λ 2 − 2λ + 1 which has a double zero at λ = 1. Hence this example gives an instance of the necessity of the condition for uniform boundedness given in [4], and in addition a counterexample to Conjecture 1 of [19], which suggested that the condition in [4] would be unnecessary.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation